2011
DOI: 10.1063/1.3647627
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free ternary perovskite compounds with large electromechanical strains

Abstract: Articles you may be interested inComposition induced structure evolution and large strain response in ternary Bi0.5Na0.5TiO3-Bi0.5K0.5TiO3-SrTiO3 solid solution Growth and orientation dependence of electrical properties of 0.92Na0.5Bi0.5TiO3-0.08 K0.5Bi0.5TiO3 lead-free piezoelectric single crystal Effect of lattice occupation behavior of Li+ cations on microstructure and electrical properties of (Bi1/2Na1/2)TiO3-based lead-free piezoceramics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 20 publications
(24 reference statements)
0
34
2
Order By: Relevance
“…The Nb0.75 and Nb1.0 shows somewhat similar behavior, may be due to small compositional difference. The majority of BNTbased systems have required high driving fields to achieve high EFIS and S max /E max ≥ 600 pm/V [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Table 1 compares the S max and corresponding S max /E max values of BNBTNb-SZ ceramics with previously reported BNT-based ceramics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nb0.75 and Nb1.0 shows somewhat similar behavior, may be due to small compositional difference. The majority of BNTbased systems have required high driving fields to achieve high EFIS and S max /E max ≥ 600 pm/V [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Table 1 compares the S max and corresponding S max /E max values of BNBTNb-SZ ceramics with previously reported BNT-based ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have attempted to lower this E th and improve the electric field-induced strain (EFIS) response [17][18][19][20][21][22][28][29][30][31][32][33][34][35][36]. Doping of impurities, either on the A-or Bsites of the ABO 3 perovskite structure, has been found as an effective method to enhance EFIS [19,[25][26][27][28].…”
Section: Introduction Q3mentioning
confidence: 99%
“…[15][16][17] Another common method has been forming solid solutions of BNT-BKT with end members that are unstable in ambient processing conditions, such as Bi(Mg 0.5 Ti 0.5 )O 3 or Bi(Ni 0.5 Ti 0.5 )O 3 . 18 Previously, it was shown that when BNT-BKT is combined with increasing concentrations of Bi(Zn 0.5 Ti 0.5 )O 3 (BZT), a transition from normal ferroelectric behavior to a material with large electric field induced strains was observed. 19,20 The higher BZT containing compositions are characterized by large hysteretic strains (>0.3%) with no negative strains that might indicate domain switching.…”
mentioning
confidence: 99%
“…Moreover, BaTiO 3 -BiInO 3 solid solutions have been studied by Datta et al; however, only a detailed structural analysis was reported [18]. Often, solid solutions of ternary compounds exhibit an improved performance compared to binary compounds, for example, BaTiO 3 -(Bi 1/2 Na 1/2 )TiO 3 -(K 1/2 Na 1/2 )NbO 3 [19], (Bi 1/2 Na 1/2 )TiO 3 -(Bi 1/2 K 1/2 )TiO 3 -Bi((Ni/Mg) 1/2 Ti 1/2 )O 3 [20], BiScO 3 -BaTiO 3 -(Bi 1/2 K 1/2 )TiO 3 [21], and BaTiO 3 -Bi(Zn 1/2 Ti 1/2 )O 3 -BiScO 3 [22].…”
Section: Introductionmentioning
confidence: 99%